IDENTIFIKASI KEMAMPUAN KOGNITIF SISWA DALAM HASIL BELAJAR AUTOCAD KELAS XI DI SMKN 56 JAKARTA (LPPM Universitas Negeri Jakarta, 2019)
This study aims to identify students' cognitive abilities in learning outcomes of AutoCAD grade XI, on the subject of Drawing with Software I `n Major Building Engineering Program at SMK Negeri 56 Jakarta. This research was conducted for six months from February 2018 until July 2018 consisting of three stages: preparing phase , implementation phase, and data processing phase. Type of research used in this research is descriptive quantitative research. The method used is survey method. Population in this research is student of class XI SMK Negeri 56 Jakarta Major Building Engineering Program that is as much as 61 student. Sample in this research use saturated sample, that is using all amount of population which is student of class XI counted 61 student. The results showed that: Based on the results of this study obtained the percentage of cognitive abilities of students in class XI in the learning result AutoCAD at Major Building Engineering Program SMK Negeri 56 Jakarta. The cognitive percentage value of class XI TGB is Remembering (C1) is 72.13%, Understanding (C2) of 62,3%, and Applying (C3) of 59.51%. So it is concluded that the average cognitive mastery ability of grade XI students in AutoCAD learning result is 64.64% and it is good.